Neutrophil-specific expression of JAK2-V617F or CALRmut induces distinct inflammatory profiles in myeloproliferative neoplasia - Haage, Tobias Ronny; Charakopoulos, Emmanouil; Bhuria, Vikas; Baldauf, Conny Katrin; Korthals, Mark; Handschuh, Juliane; Müller, Peter; Li, Juan; Harit, Kunjan; Nishanth, Gopala; Frey, Stephanie; Böttcher, Martin; et al. (Journal of hematology & oncology, 2024)
Background: Neutrophils play a crucial role in inflammation and in the increased thrombotic risk in myeloproliferative neoplasms (MPNs). We have investigated how neutrophil-specific expression of JAK2-V617F or CALRdel re-programs the functions of neutrophils. Methods: Ly6G-Cre JAK2-V617F and Ly6G-Cre CALRdel mice were generated. MPN parameters as blood counts, splenomegaly and bone marrow histology were compared to wild-type mice. Megakaryocyte differentiation was investigated using lineage-negative bone marrow cells upon in vitro incubation with TPO/IL-1β. Cytokine concentrations in serum of mice were determined by Mouse Cytokine Array. IL-1α expression in various hematopoietic cell populations was determined by intracellular FACS analysis. RNA-seq to analyse gene expression of inflammatory cytokines was performed in isolated neutrophils from JAK2-V617F and CALR-mutated mice and patients. Bioenergetics of neutrophils were recorded on a Seahorse extracellular flux analyzer. Cell motility of neutrophils was monitored in vitro (time lapse microscopy), and in vivo (two-photon microscopy) upon creating an inflammatory environment. Cell adhesion to integrins, E-selectin and P-selection was investigated in-vitro. Statistical analysis was carried out using GraphPad Prism. Data are shown as mean ± SEM. Unpaired, two-tailed t-tests were applied. Results: Strikingly, neutrophil-specific expression of JAK2-V617F, but not CALRdel, was sufficient to induce pro-inflammatory cytokines including IL-1 in serum of mice. RNA-seq analysis in neutrophils from JAK2-V617F mice and patients revealed a distinct inflammatory chemokine signature which was not expressed in CALR-mutant neutrophils. In addition, IL-1 response genes were significantly enriched in neutrophils of JAK2-V617F patients as compared to CALR-mutant patients. Thus, JAK2-V617F positive neutrophils, but not CALR-mutant neutrophils, are pathogenic drivers of inflammation in MPN. In line with this, expression of JAK2-V617F or CALRdel elicited a significant difference in the metabolic phenotype of neutrophils, suggesting a stronger inflammatory activity of JAK2-V617F cells. Furthermore, JAK2-V617F, but not CALRdel, induced a VLA4 integrin-mediated adhesive phenotype in neutrophils. This resulted in reduced neutrophil migration in vitro and in an inflamed vessel. This mechanism may contribute to the increased thrombotic risk of JAK2-V617F patients compared to CALR-mutant individuals. Conclusions: Taken together, our findings highlight genotype-specific differences in MPN-neutrophils that have implications for the differential pathophysiology of JAK2-V617F versus CALR-mutant disease.